High genetic diversity of hepatitis delta virus in eastern Turkey - Bulut, Yasemin; Bahcecioglu, Ibrahim Halil; Aygun, Cem; Oner, Pinar Demirel; Ozercan, Ibrahim; Demirdag, Kutbeddin (J Infection Developing Countries, 2014)
Introduction: Hepatitis delta virus (HDV) is a serious cause of liver-related mortality in patients infected with hepatitis B virus (HBV). Determination of genotypes of HDV and phylogenetic analysis are important for better understanding the pathogenesis of the liver diseases associated with HBV infection. The aim of this study was to determine the genotype or genotypes of HDV among chronically infected patients with HBV in eastern Turkey. Methodology: A group of 113 patients infected with HBV and HDV were included in this study. The samples taken from the patients were analyzed by reverse transcriptase-polymerase chain reaction (RT-PCR) and restriction enzyme cleavage. Results: According to the results of the restriction enzyme analysis, all of the RT-PCR products were determined to be HDV genotype I. Furthermore, for phylogenetic analysis and genotyping, 40 of HDV RT-PCR positive products were sequenced. Phylogenetic analysis of the sequences showed that all of the samples were infected with HDV genotype I. In addition, the results of the alignment analysis showed that the sequences of clinical samples were 82%-95% similar. Conclusion: These results indicate that high genetic diversity of the virus is possible in endemic areas such as Turkey.
Keywords: hepatitis delta virus; hepatitis B virus; genotyping; restriction enzyme analysis; phylogenetic analysis